PENGARUH BRAND IMAGE AIR ASIA TERHADAP KEPUTUSANPEMBELIAN TIKET MASKAPAI PENERBANGAN PADA KONSUMEN PEGANGSAAN DUA - Siti Meisyaroh (Jurnal Ekonomi Perusahaan, 2017)
The objective of this research is to analyze the influence of brand image on purchase decision. Researcher finds the problem when the airlines start the development in Indonesia, one of them is Air Asia. Air Asia is a company which provides airlines transportation service, besides it is awarded by Skytrax as The World’s Top Low-Cost Airlines of 2016. Researcher wants to know that the brand image of Air Asia as low cost airline influences the consumer purchase decision of airline ticket in Pegangsaan Dua, North Jakarta region.This research uses concept of marketing communication, cover brand image and consumer purchase decision. By those concepts it can be understood the factors in variable which researcher choose. Researcher try to analyze how big consumer decision in airline ticket purchasing was influenced by Air Asia brand image.The method used is quantitative method with descriptive approach. This research took brand image of AirAsia as the research object. In the study author collected data through questionnaires that distributed to 100 respondents who were in the area Pegangsaan Dua, North Jakarta. Questionnaire data that have been obtained, then processed with SPSS 20.0.The method of this research showed that the distribution of the data is normal. By this research it will be showed that there’s influence of Air Asia brand image on consumer purchase decision of airline ticket in Pegangsaan Dua, North Jakarta region is 37,2%.Conclusion of this research is the value of product or service in consumer’s mind can influences consumer purchase decision. In this research it is showed that besides the brand image, sales promotion is also the other factor which can influences consumer purchase decision of airline ticket. Keywords: Brand Image, Purchase Decision, Airline Ticket